Role of Lemna minor (L.) plant in change of pH values of Aquatic system - Sharba, Furqan Yahya Jawad; Mohammed, Zainab Abd Ameer; Salman, Furqan Saddam; Zwayen, Taghreed Fakhir Gaber (Journal La Lifesci, 2024)
The current study documented the ability of Lemna minor plants floating in the Shatt Al-Kufa / Euphrates River and grown invitro to affect in pH water, as the results showed wide variation in readings. Highest value recorded in the 1st week with 8 at T2 and T3, while the lowest value was in the 2nd and 3rd week with only 6.9 at T3 and T1 respectively. The T1 treatment of understudy plant was unique from the rest of the treatments, by continuing in decline the water pH values until the end of the experiment. The reasons for the increase or decrease pH values of water are attributed to the Lemna minor content of some minerals and the absence of other minerals.